Effect of a 26-month floorball training on male elderly's cardiovascular fitness, glucose control, body composition, and functional capacity - Mogens Theisen Pedersen; Jacob Vorup; Jens Bangsbo (Elsevier, 2018)
Background: Floorball training offers a motivating and socially stimulating team activity for older adults, and 12 weeks of floorball training twice a week among men aged 65-76 years have been shown to have positive effects on a number of physiological parameters important for health. However, the effect of long-term participation in floorball training among male elderly has not been investigated. The aim of the present study was to examine the effect of 26-month self-organized regular participation in floorball training on cardiovascular fitness, body composition, blood lipids, glucose control, and physical function among recreationally active men aged 66-78 years. Methods: After completing a 12-week randomized and controlled intervention with floorball and petanque training in the autumn 2014 or spring 2015, 15 subjects chose to participate in floorball training (floorball group, FG), whereas 16 subjects resumed their usual lifestyle (control group, CG). FG took part in self-organized floorball training 1.7 sessions of 40 min/week, and CG continued their normal recreationally active lifestyle during a 26-month follow-up period. At baseline and after the follow-up period subjects were tested for cardiovascular fitness, glucose control (resting blood samples), body composition dual-energy X-ray absorptiometry (DXA-scanning), and functional capacity. Results: In FG, the decline in maximal oxygen uptake (VO2max) during the follow-up period was lower (242 ± 379 mL/min, p = 0.01), blood glycosylated hemoglobin (HbA1c) increased less (−1.6 ± 2.9 mmol/L, p = 0.02), and leg bone mineral density increased more (0.03 ± 0.05 g/cm2, p = 0.02) than those in CG. The effects on body mass, total lean body mass, fat mass, blood lipids, and physical function were similar in FG and CG. Conclusion: Approximately twice weekly floorball sessions with 40 min/session over 26-month appear to reduce age-related decline in cardiovascular fitness and glucose control and improve leg bone mineral density, suggesting that long-term participation in floorball training can be considered as a health-enhancing activity in recreationally active male elderly. Keywords: Bone mineral density, Elderly, Floorball, Glucose control, VO2max